SAT0174 Clinical and Histological Features in Patients with Permanent Visual Los Due to Biopsy-Proven Giant Cell Arteritis. (23rd January 2014) - Solans-Laqué, R.; Fraile, G.; Monteagudo, M.; Caminal, L.; Abdilla, M.; Fanlo, P.
Abstract : Background: Amaurosis is the most frequent ischemic complication and the main cause of permanent disability among patients with giant cell arteritis (GCA). Some premonitory symptoms of visual loss such as amaurosis fugax, diplopia and blurry vision have been described Objectives: To determine associated clinical and histological findings in patients with GCA and visual loss due to anterior ischemic optic neuropathy (AION). Methods: Demographic, clinical and histological features of patients with biopsy-proven GCA recruited at 6 different Hospitals from Spain were analyzed. Statistical analysis was performed using the SPSS vs. 17. Results: There were 135 patients, 82 (60.7%) females and 53 (39.3) males, with a mean age of 74.9 ± 7 (58-89) at diagnosis. Cardiovascular risk factors were present in 45% of cases (hypertension in 40%, hypercholesterolemia in 20%, diabetes mellitus in 18.5%, and smoking habit in16.2%). The most frequent symptoms at CGA diagnosis were recent-onset headache (83%), jaw claudication (37%), cranial hyperesthesia 55 (40.7%) and constitutional symptoms (48.1%). Polymyalgia rheumatica was present in 50.4% of cases. Sixteen patients had lost vision due to AION, two of them involving both eyes. Sixty-two percent of patients complained of classical GCA cranial symptoms for an average of 7 weeks (range 2 days to 16 weeks). Seven (43.8%) patients had premonitory visual symptoms before visual loss. Six patients had an apparent isolated polymyalgia rheumatica for an average of 14 months (range 6 to 24 months). Mean ESR was 99 (28-163). 76.3 of patients had anemia. No significant relationship was found between visual loss development and cardiovascular risk factors. AION was significantly related to the presence of amaurosis fugax (p=0.002), jaw claudication (p=0.025) and temporal artery abnormalities on physical examination (p = 0.04). In addition, the presence of giant cells in temporal artery biopsy (p = 0.004), inflammatory infiltrate (p=.0.001) and elastic membrane disruption (p= 0.020), were significantly most frequent in patients with AION. Conclusions: A high proportion of patients with permanent visual loss have a delayed diagnosis and treatment. A wider recognition of the disease would potentially reduce the prevalence of irreversible visual loss among GCA patients. References: Font C et al. Clinical features in patients with permanent visula loss due to biopsy-proven giant celll arteritis. Br J Rheumatol 1997 Makkuni D. Is intimal hyperplasia a marker of neuro-opthalmic complications of giant cell arteritis?. Rheumatol 2008 Disclosure of Interest: None Declared